Estimation of serum and follicular fluid Malondialdehyde among women undergoing IVF: Association with age, duration of subfertility and other IVF outcome parameters. - Journal, IMR (International Multidisciplinary Research Journal, 2014)
Background: Oxidative stress affects various functions in female reproduction and its role in female infertility is proposed. Hence it was of interest to analyze serum and follicular fluid (FF) Malondialdehyde (MDA) among women undergoing IVF and determine its association with IVF outcome determinants (age, subfertility duration, type of stimulation protocol used, fertilization potential of oocytes, embryo quality and post-IVF pregnancy). Materials and Methods: FF collected by transvaginal ultrasound guided oocyte rupture and IV blood from 28 women (20-40years) undergoing IVF/ICSI, were analyzed for MDA following TBARS method and its association with IVF outcome parameters were compared. Results: Mean MDA was significantly higher in serum than FF among all women tested (2.98 ± 0.14 Vs 2.23 ± 0.11; P=0.0001), IVF group (2.88 ± 0.16 Vs 2.25 ± 0.16; p =0.008) and ICSI group (3.10 ± 0.23 Vs 2.20 ± 0.15; P=0.005). No significant association was seen between MDA and other parameters except embryo quality (r=0.378, p=0.047). Conclusion: Low MDA in FF compared to serum evidences that FF has an effective antioxidant mechanism to overcome oxidative stress. The importance of ROS in female reproduction is evidenced by positive correlation between MDA and embryo quality.